A Simplistic Review of the Soundex Algorithm: The Magic of Phonetics - Vishal Paul Jeosuva; Rajesh Ramnaresh Yadav (International Journal of Algorithms Design and Analysis Review, 2024)
As a human, we always make mistakes while pronouncing words, names, and terms that sound alike. As a result of which those spellings are difficult to identify. To simplify this problem, we have discussed an algorithm called Soundex algorithm which provides a solution to pronunciation problems by giving a similar code with 1-letter and 3-digit code as a syntactical solution to all terms that sound alike. In this study, we have discussed the following sections to give a brief overview: introduction, history, literature review of algorithmic rules, Python-based implementation, real-life applications, key benefits, limitations, and conclusion.
Keywords: Pronunciation; Robert Russell; Similar Spellings; Soundex